Constitutional Framework of Good Governance under the Islamic Legal System - Alomran, Nayel (DIRASAT: SHARI'A AND LAW SCIENCES, 2019)
Some states have been criticised in a number of ways for their perceived lack of good governance, political injustice and the dictatorial system of the government. This article is an attempt to discover theories and principles of good governance in the Islamic legal system. It is also an attempt to cover some of the important principles which are relevant to discourse on Islamic politics and how these principles can be used to establish good governance in Islamic states. This article also attempts to observe the incorporation of constitutional framework of good governance under Islamic law. To argue this case, the author employs the historical and descriptive analytical method to search within the Islamic heritage for illustrative examples from history and the Islamic civilization.